The Effect of “Insufficient Milk Supply” Concept Intervention on Mother's Perception of Breast Milk Production - Mekar Dwi Anggraeni; Lutfatul Latifah; Ima Rismawati (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2016)
Background: World Health Organisation (WHO) recommends every mother to provide exclusive breastfeeding for their infants because of its benefits. However the exclusive breastfeeding rate in Indonesia was only 35%in 2013. One of the main factors affecting low exclusive breastfeeding rate was maternal perception of having low breastmilk supply. There were no previous studies examining the effect of "Insufficient Milk Supply" concept intervention on mother’s perception of low breastmilk production. This research was an innovation in nursing.Aim: To investigate the effect of intervention program based on “Insufficient Milk Supply” concept on mother’s perception of low breastmilk supply.Methods: This study was a quasy experiment pretest-posttest. Postpartum mothers were provided an intervention using a module based on the concept of "Insufficient Milk Supply". The perception of breastmilk production was measured using the Nine-items of Lactation Scale. Data were analyzed using independent t test and paired t test.Results: The t test assumptions were examined and yielded that the data were normally distributed and the variances were homogeneous. The results showed there were significant differences between the scores of pre- and post-test in the intervention group (t = -9,03, p < 0.001).Conclusion: This study offers evidence that Insufficient Milk Supply can be used in nursing practice as a concept to improve the perception of the mother's breastmilk supply.